IT DOES NOT TAKE A PROPHET: WAR AND PEACE IN THE CAUCASUS - TCHANTOURIDZE, Lasha (CENTRAL ASIA AND THE CAUCASUS, 2009)
Was the August 2008 war between Russia and Georgia, which resulted into a dismemberment of Georgia, predictable and avoidable? Supporters and ideological allies of the current Georgian government have insisted that those who criticize the alertness and behavior of the Saakashvili administration are looking at this issue with the full benefits of hindsight. To be fair, political scientists are much better at predicting the past than the future, and if we follow this logic, the future conflicts between the two neighbors in the Caucasus should be as “unpredictable” and “unexpected’ as this one.The international system behaves very much like a stochastic system, but it does exhibit certain regularities and carries certain continuity when it comes to behavior of its actors. Despite weaknesses and problems unleashed by the era of globalization, nation-states remain the main actors of the international system. Survival continues to be the main value for these actors, and the system guides the nation-states or those who act on their behalf to do their utmost to preserve this value for themselves and stay as actors in the system. States compete, jostle, combine, and sometimes even collide in order to accumulate enough power and capabilities to provide for their survival. States collide and fight not because they have different values in the international system, but as carriers of the same set of values they come to different understandings and perspectives of how to defend these values based on their individual geopolitical circumstances. Therefore, states may develop different, and often competing interests around the same issue, which occasionally throws them into violent conflicts